Klinefelter syndrome: a comprehensive review beyond the 47 XXY karyotype (2023)
Klinefelter syndrome is a pathological condition caused by a chromosomal aberration in males, resulting in the most common alteration of sex chromosomes in humans, characterized by a karyotype of 47 XXY. Its prevalence ranges from 85 to 250 cases per 100,000 live births annually. The absence of clinical signs during early decades of life often leads to a delayed diagnosis, which is associated with metabolic, vascular, and hormonal alterations that negatively impact individuals with this condition. Due to the high prevalence and underdiagnosis of Klinefelter syndrome, it is crucial to understand the genetic and epigenetic processes underlying the disease's development and recognize the accompanying clinical signs. A systematic review of literature was conducted in major medical research databases to achieve this objective. After applying inclusion criteria, 50 relevant articles were analyzed and consolidated to create an updated document. This comprehensive review serves as an important guide for understanding and approaching patients with Klinefelter syndrome, based on scientific evidence. By enhancing awareness and knowledge about this complex medical condition, healthcare professionals can improve early diagnosis, intervention, and management strategies for individuals affected by Klinefelter syndrome.